2018
DOI: 10.1371/journal.pone.0195435
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with death and loss to follow-up in children on antiretroviral care in Mingalardon Specialist Hospital, Myanmar, 2006–2016

Abstract: BackgroundMyanmar National AIDS programme’s priority is to improve the survival of all people living with HIV by providing anti-retroviral therapy (ART) care. More than 7200 children (aged <15 years) have been enrolled into ART care from 2005 to 2016. A previous study showed that ~11% children on ART care had either died or were lost to follow-up by 60 months. Factors associated with death and lost-to follow-up (adverse outcomes) have not been previously studied.ObjectivesTo describe the association between de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 3 publications
(2 reference statements)
5
8
4
4
Order By: Relevance
“…Finally, children who started PI-based ART regimens were at higher risk of LTFU as compared to those who started non-nucleoside reverse transcriptase inhibitors (Nevirapine or Efavirenz) based ART regimens. This finding contradicts a previous study done in Myanmar [ 28 ]. This variation could be due to the baseline differences between study participants at ART initiation, leading to the prescription of PI-based regimens.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Finally, children who started PI-based ART regimens were at higher risk of LTFU as compared to those who started non-nucleoside reverse transcriptase inhibitors (Nevirapine or Efavirenz) based ART regimens. This finding contradicts a previous study done in Myanmar [ 28 ]. This variation could be due to the baseline differences between study participants at ART initiation, leading to the prescription of PI-based regimens.…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence density of LTFU in this study was estimated to be 4.5 (95% CI: 3.5, 5.7) per 100 child-years of observation. Our finding is in line with studies done in South Africa (5.0 per 100 child-years) [ 27 ], Myanmar (4.7 per 100 child-years) [ 28 ], and Asia and Africa (4.1 per 100 child-years) [ 29 ]. Conversely, our finding is much lower than studies conducted in India (14.4 per 100-child years) [ 30 ], South Africa (10.8 per 100 child-years) [ 31 ], Tanzania (18.2 per 100-child years) [ 32 ], multicountry study (14.2 per 100-child years) [ 33 ], Malawi (12.6 per-100 child-years) [ 19 ], and Ethiopia (6.22 per 100 child-years) [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In 2014, the NAP launched a new service delivery model to reach urban PLHIV and key populations through clinic-based testing and treatment sites in partnership with iNGOs called ART satellite sites. Several studies have reported retention in care with rates ranging from (30 to 90%) (711). There have been no previous studies assessing the outcomes of PLHIV on ART at ART satellite sites in Myanmar.…”
Section: Background and Rationalementioning
confidence: 99%